Effectiveness microbes (em) and compost as a fertilizer for enhancement soil - Nor Amanina Binti Osli (School of Environmental Engineering, University Malaysia Perlis, 2016)
The use of the new technology of composts, namely Indigenous Microbe (IMO) and the enzymes from a natural farming technologies (such as Effective Microbes (EM) and Arbuscular Mycorrhizzal Fungi (AMF)) are become more favourite as compare to the traditional composts. The EM fertilizer is a combination of beneficial micro-organisms that has been created by Professor Teruo Higa at the University of the Ryukyus, Japan. The traditional composts are made from the household wastes on the chemical, physical and biological characteristics of soil with a long use history are evaluated. The study is included the performance of the EM and the traditional composts as the good soil enhancers. The study also investigated about the preferred country that applies the enhancers and the chemical properties that contained in both fertilizers. The study are conducted by collecting the secondary data, which is the data from the journal, book and etc. The results showed that the EM fertilizer are a most practiced in Japan and the most preferred chemical properties in the both fertilizer are potassium, nitrogen and phosphorus. In general, the results can conclude that the EM are the most effective as a fertilizer for enhancing soil, as compared to the composts.